Ganoderma tuberculosum Liquid Culture With Vineyard Pruning Extracts for Bioactive Composite Production With Antiproliferative Activity - Lucia T. Angulo-Sanchez; María C. Cruz-Félix; Max Vidal-Gutiérrez; Heriberto Torres-Moreno; Óscar A. Muñoz-Bernal; Emilio Álvarez-Parrilla; Ramón E. Robles-Zepeda; Osiris Álvarez-Bajo; Aldo Gutiérrez; Martín Esqueda (Advances in Pharmacological and Pharmaceutical Sciences)
Ganoderma species have been studied for their pharmacological approaches, such as anticancer, antitumor, antiproliferative, and antioxidant activity. Elicitors are used to increase Ganoderma bioactive composite production. This study aims to evaluate the antiproliferative activity of ethanolic extracts from mycelium of Ganoderma tuberculosum (G. tuberculosum) grown in a liquid medium with vineyard pruning waste (VPW) extracts as elicitors. Ethanolic and aqueous VPW extracts contain resveratrol dimer 4, resveratrol tetramer 1, and naringenin, while toluene and chloroform extracts contain tetradecanoic acid, hexadecanoic acid, and octadecanoic acid. Polar and nonpolar extracts could be promising elicitors for increasing bioactive molecules. Catechin gallate showed the highest correlation (r = 0.66) with biomass. Mycelial ethanolic extracts of G. tuberculosum (native strain from the Sonoran Desert) and Ganoderma lucidum (G. lucidum) (control) were analyzed by ESI-IT-MS, and 27 molecules were identified for the two species. They showed antiproliferative activity against the A549 and C-33 A cell lines but not for ARPE-19. G. tuberculosum culture with VPW had quinic acid, ganodermenonol, ganoderic acid I (GA-I), C2 (GA-C2), and 20-hydroxylucidenic acid P, among others. Molecular docking of ganodermenonol, GA-I, and GA-C2 demonstrates significant interaction with tumor necrotic factor (TNF-α). These ethanolic extracts of Ganoderma are promising sources of bioactive triterpenoids. Their antiproliferative activity did not change between species or treatment. Likewise, the G. tuberculosum and G. lucidum extracts only affected cancer cell lines. This property seems promising for pharmacological applications of these fungal extracts.